ESG and Cash Holdings: An Empirical Study of Chinese Listed Firms - Ma,Kun; Xue,Ziyi (2025)
As the climate crisis has intensified in the 21st century, the role of ESG has become increasingly important in the international community. As the largest developing country, China has also been actively promoting ESG development. In September 2020, at the United Nations Climate Summit, China announced its “dual carbon” targets—to reach peak carbon emissions by 2030 and achieve carbon neutrality by 2060. Cash, often regarded as the lifeblood of a company, plays a critical role in ensuring corporate survival and operational stability, making cash management a key aspect of corporate decision-making. Therefore, this study explores the relationship between ESG performance and corporate cash holdings. Based on data from Chinese A-share listed companies from 2014 to 2023, this paper investigates the direct impact and underlying mechanisms of ESG on corporate cash holdings from the dual perspectives of precautionary motives and agency motives. We conduct a regression analysis, incorporating year and industry fixed effects to improve the accuracy and robustness of the model estimates, and find that ESG has a positive impact on corporate cash holdings. Through further moderation analysis, we use the market-to-book ratio (MTB) to measure investment opportunities and employ dividend payout and firm size to measure external financing costs. The results show that the positive effect of firms’ ESG performance on corporate cash holdings is strengthened through the investment opportunity channel and weakened through the external financing cost channel, according to the precautionary motive. In addition, we conduct a mediation analysis using the proportion of shares held by management as a measure of the agency motive. We find that good ESG performance can alleviate agency problems, thereby negatively affecting cash holdings. However, in the Chinese context, this negative effect of agency motives is offset by the positive effect of precautionary motives, resulting in an overall positive impact of ESG on cash holdings. Finally, this study further divides the sample based on ownership type to conduct a heterogeneity analysis, and the results show that ESG has a stronger positive effect on cash holdings in non-state-owned enterprises compared to state-owned ones. This research enriches the theoretical framework of corporate cash holding decisions and, by incorporating China’s unique institutional context, explains the mechanisms through which ESG influences cash holdings, thereby supplementing empirical studies in emerging markets.
Keywords: ESG; Corporate Cash Holdings; Precautionary Motive; Agency Problem